PENGARUH ETOS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. POS INDONESIA (PERSERO) CABANG BATURAJA - Dwi Septi Listiyaningsih; Noviansyah .; Rani Anwar (Ekonomika, 2024)
This research aimed to determine the influence of work ethic and work environment on employees' performance at PT. Pos Indonesia (Persero) Baturaja Branch. The data used was primary data through questionnaires and a population of 30 employees. The analysis used was multiple linear regression, t test, f test, and analysis of the coefficient of determination. The results of data analysis showed that Work Ethic and work environment influencedPT. Pos Indonesia (Persero) Baturaja Branch, either partially or simultaneously. The results of the coefficient of determination showed that the contribution of the influence of Work Ethic and Work Environment together on employees' performance was 89.7%, while the remaining 10.7% was influenced by other variables. For companies so that PT. Pos Indonesia (Persero) Baturaja Branch continued to improve its human resource (HR) capabilities in an effort to provide satisfaction or services to the community.